Study of Nd203-CuO-P205 glass system by elastic properties - Budi, Agus Setyo; Russin, Rosli; Sahar, Md. Rahim (Faculty of Science, UTM, 2003)
Longitudinal and shear ultrasonic velocities were measured in different compositions of the glass system Nd203(x)CuO(35-x)P205(65) at temperature range between 270 K and 323 K. From the transit time data and density, we found that all the elastic properties for these glasses decrease as the Nd203 content increase, which indicates a weakening ofthe binding energy in the network.